The Effect of Dark Leadership Traits on Employee Job Embedded: A Chain Mediation Analysis of Leader-Member Exchange and Perceived Insider Status - Shahzadi, Shazia; Mahar, Sourath; Mahar, Abdul Qayoom; Ullah, Naqeeb; Baloch, Qadar Bakhsh (2024)
The study focus on dark leadership traits (narcissistic, psychopathic, and Machiavellian), highlights the negative effects on employee job embeddedness, and emphasizes the mediating roles of Leader-Member Exchange and Perceived Insider Status. Leadership characterized by narcissistic, psychopathic, or Machiavellian traits collectively referred to as "dark leadership" that integrates self-serving behaviors with manipulative tendencies, often driven by arrogance and personal gain. This style of leadership can have profound negative impacts on both organizations and their employees. The growing interest in understanding the detrimental effects of dark leadership on subordinates has become a focal point in organizational behavior research. This study, grounded in social exchange theory and resource conservation theory, develops a chain mediation model to examine how dark leadership influences employee job embeddedness. Utilizing data from a survey of 405 corporate employees, the study's findings reveal a significant negative relationship between dark leadership traits and job embeddedness. Additionally, leader-member exchange (LMX) and perceived insider status are shown to act as mediating variables in this relationship, both independently and in a chain mediation framework. These findings offer valuable insights into the complex dynamics of dark leadership, contributing to the theoretical understanding of its impact and providing practical implications for improving leadership practices across various organizational contexts.